Teamwork as a self-disciplining device - Matthias Fahn; Hendrik Hakenes (Johannes Kepler University of Linz, Department of Economics, 2017)
We show that team formation can serve as an implicit commitment device to overcome problems of self-control. If individuals have present-biased preferences, effort that is costly today but rewarded at some later point in time is too low from the perspective of an individual's long-run self. If agents interact repeatedly and can monitor each other, a relational contract involving teamwork can help to improve performance. The mutual promise to work harder is credible because the team breaks up after an agent has not kept this promise - which leads to individual underproduction in the future and hence a reduction of future utility.
Keywords: L22; L23; 330; Self-Control Problems; Teamwork; Relational Contracts